2014
DOI: 10.1177/0305735614557990
|View full text |Cite
|
Sign up to set email alerts
|

The influence of musical training on acculturation processes in migrant children

Abstract: Music is a promising candidate for the enhancement of cultural integration through increased group cohesion and social support. This study assessed the impact of a music program on elementary schoolaged migrants' cultural orientation, as measured via the Frankfurt Acculturation Scale for Children . The music program is an extension of schools' regular curriculum and provides students with basic introduction to music and instrument lessons (Years 1 and 2), followed by school-wide music performances within an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 47 publications
3
26
0
7
Order By: Relevance
“…In addition, songs that the older immigrants sing and listen to provided extensive information about each individual's personhood-who they are, where they come from, what they feel in specific moments, and what they like and dislike-, which aligns with the notion of songs as a symbol to elaborate a sense of self and to tell the "continuous" stories of who they are (DeNora, 1999). As previous studies indicated that young immigrants often used music from their homeland to maintain a continuity of their previous selves (e.g., Frankenberg et al, 2014;Karlsen, 2012Karlsen, , 2013 and cultivate the collective identity of their larger cultural/ethnic groups in the immigrant societies (e.g., Karlsen & Westerlund, 2010), songs of the older immigrants in this study seemed to significantly contribute to their personal, as well as collective, identity works. However, although young immigrants also used music as a tool to cultivate their "fluid, multilayered self " by relating themselves to the popular music of general youth culture, which is the commonality of interests with their peers of the host society, this did not appear in any cases in the narratives of the elderly interviewees.…”
Section: Concluding Thoughtssupporting
confidence: 67%
See 3 more Smart Citations
“…In addition, songs that the older immigrants sing and listen to provided extensive information about each individual's personhood-who they are, where they come from, what they feel in specific moments, and what they like and dislike-, which aligns with the notion of songs as a symbol to elaborate a sense of self and to tell the "continuous" stories of who they are (DeNora, 1999). As previous studies indicated that young immigrants often used music from their homeland to maintain a continuity of their previous selves (e.g., Frankenberg et al, 2014;Karlsen, 2012Karlsen, , 2013 and cultivate the collective identity of their larger cultural/ethnic groups in the immigrant societies (e.g., Karlsen & Westerlund, 2010), songs of the older immigrants in this study seemed to significantly contribute to their personal, as well as collective, identity works. However, although young immigrants also used music as a tool to cultivate their "fluid, multilayered self " by relating themselves to the popular music of general youth culture, which is the commonality of interests with their peers of the host society, this did not appear in any cases in the narratives of the elderly interviewees.…”
Section: Concluding Thoughtssupporting
confidence: 67%
“…While music is often considered to be a promising medium with which to facilitate the process of immigrants’ acculturation (Frankenberg et al, 2014), music education studies have shown how music, “as an integral part of human experience” (Marsh, 2013, p. 508), specifically plays a role in fostering immigrant children and adolescents’ successful cultural integration into their new environment (e.g., Gilboa, Yehuda, & Amir, 2009; Karlsen & Westerlund, 2010; Marsh, 2013; O’Hagin & Harnish, 2006; Sæther, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…En este sentido, se ha comprobado el poder de la música para el desarrollo del bienestar emocional, las habilidades sociales y el sentido de pertenencia (Cabedo-Mas, 2015;Chandal & Levitin, 2013;Frankenberg et al, 2016;Hallam, 2010;Zapata, 2011). Incluso, dice Maclean (2011, p. 11), "cuando los participantes experimentan un sentido de propósito compartido se libera oxitocina, un neuroquímico involucrado en el establecimiento de la confianza".…”
unclassified